Intermittent Use of Flash Glucose Monitoring Improves Glycemic Control in Chinese Older Patients with Type 2 Diabetes Mellitus - Hu Y; Yan R; Shen Y; Li H; Ma J; Su X (Diabetes, Metabolic Syndrome and Obesity)
Yonghui Hu,* Rengna Yan,* Yun Shen, Huiqin Li, Jianhua Ma, Xiaofei Su Department of Endocrinology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhua Ma; Xiaofei Su, Email majianhua196503@126.com; suxiaofeifei@126.comObjective: To explore the efficacy and safety of intermittent use of flash glucose monitoring (FGM) for improving glycemic control in Chinese elderly patients with type 2 diabetes mellitus (T2DM).Methods: This is a prospective observational study involving patients with T2DM aged ≥ 60 years. The study period spans 12 weeks, with participants wearing FGM at weeks 0, 5, and 10. Participants were divided into two subgroups based on HbA1c at enrollment: < 7.0% and ≥ 7.0%. The primary outcome of the study was HbA1c level. Secondary outcomes included time in range (3.9– 10mmol/L) (TIR), time below range (< 3.9mmol/L) (TBR), time above range (> 10.0mmol/L) (TAR), and glycemic variability (GV).Results: A total of 68 patients completed the 12-week FGM follow-up (age 67.9 ± 5.2 years; BMI 25.4 ± 3.3kg/m²). Overall findings revealed that compared to baseline, HbA1c decreased from 7.81 ± 1.25% to 7.44± 1.10% after 12 weeks of intermittent wearing of FGM (p < 0.001). In the subgroup analysis with HbA1c ≥ 7.0%, the results showed a significant reduction in HbA1c of 0.51mmol/L after 12 weeks (8.36 ± 0.95% vs 7.75 ± 0.97%, p < 0.001). And there was a significant reduction in TBR in the subgroup with HbA1c < 7% (p = 0.028). Multiple linear regression analysis showed that the baseline HbA1c (β = − 0.529, P< 0.001), duration of T2DM (β = 0.341, P = 0.001), and the frequency of sensor use (β = − 0.269, P = 0.043) were associated with the reduction in HbA1c level.Conclusion: Intermittent use of FGM is associated with an improvement in glycemic outcomes and reduces the risk of hypoglycemia in Chinese elderly patients with T2DM.Keywords: flash glucose monitoring, type 2 diabetes mellitus, HbA1c, time in range